Alteration of intracranial blood perfusion in temporal lobe epilepsy, an arterial spin labeling study. Issue 4 (April 2023) - Rahimzadeh, Hossein; Kamkar, Hadi; Hoseini-Tabatabaei, Narges; Mobarakeh, Neda Mohammadi; Habibabadi, Jafar Mehvari; Hashemi-Fesharaki, Seyed-Sohrab; Nazem-Zadeh, Mohammad-Reza
Abstract: Background: A critical necessity before surgical resection in mesial temporal lobe epilepsy (mTLE) is lateralizing the seizure focus in the temporal lobe. This study aimed to investigate the differences in perfusion pattern changes in right and left mTLE. Methods: 42 mTLE patients (22 left and 20 right mTLE) and 14 controls were surveyed with pulsed arterial spin labeling at 3.0 T. The mean cerebral blood flow (CBF) and asymmetry index (AI) were calculated in the bilateral temporal lobe, amygdala, hippocampus, parahippocampus, and nine bilateral vascular territories ROIs. The alterations in whole-brain CBF were identified using statistical parametric mapping (SPM). Results: CBF decreased in ipsilateral sides in both epilepsy subcohorts, with right mTLE showing a significant difference in most ROIs while left mTLE exhibiting no significant change. CBF comparison of left mTLE and controls showed a significant drop in ROI analysis in left middle temporal and left intermediate posterior cerebral artery and in AI analysis in parahippocampus, distal anterior cerebral artery, distal middle cerebral artery, and intermediate anterior cerebral artery. CBF hypoperfusion was seen in ROI analysis in the left intermediate anterior cerebral artery, left middle temporal, right middle temporal, left superior temporal in the right mTLE compared to controls. Left mTLE CBF differed significantly from right mTLE CBF in right distal middle cerebral artery ROI and AI of proximal middle cerebral artery. Conclusion: Our result revealed that mTLE affects extratemporal regions and both mTLE subcohorts with different perfusion patterns, which may enhance the performance of preoperative MRI assessment in lateralization procedures.